Determination of ferulic acid by flow injection chemiluminescence analysis based on enhancement of the N‐bromobutanimide–eosin–CrCl3 system in alkaline solution. (21st February 2013) - Shen, Guopeng; Jia, Xin; Jin, Jianwen; Pang, Li; Chen, Zheng; Du, Bin
ABSTRACT: A simple and sensitive flow injection chemiluminescence method has been developed for the determination of ferulic acid (FA) based on the significant enhancement effect of FA on the CL signal of the N ‐bromobutanimide (NBS)–eosin–CrCl3 system in alkaline solution. Under optimum conditions, the enhanced CL intensity is linearly related to the concentration of FA in its pharmaceutical preparations and human plasma samples. The corresponding linear regression equations were established over the 4.0 × 10 –10 –1.0 × 10 –7  g/mL for FA tablets and 2.0 × 10 –10 –1.0 × 10 –7  g/mL for plasma samples. The limit of detection for FA tablets and limit of quantification for plasma samples were 2.8 × 10 –10  g/mL (3 σ) and 3.04 × 10 –10  g/mL (10 σ), respectively. A complete analysis could be performed within 40 s, including washing and sampling, giving a throughput of ≈90/h. The proposed method was successfully applied to the determination of FA in pharmaceutical preparations and human plasma samples with satisfactory results. The recoveries of pharmaceutical preparations and human plasma samples at three different concentrations were 97.8–102.6% and 96.7–104.0%, respectively. Furthermore, the possible mechanism of CL reactions was also discussed briefly. Copyright © 2013 John Wiley & Sons, Ltd.